2004
DOI: 10.1002/wcm.160
|View full text |Cite
|
Sign up to set email alerts
|

A unified bandwidth reservation and admission control mechanism for QoS provisioning in cellular networks

Abstract: SummaryWe propose a unified framework consisting of a differential bandwidth reservation (DBR) algorithm and a Quality of Service (QoS)-aware admission control scheme to provide QoS guarantees to on-going connections in cellular networks. The differential bandwidth reservation policy uses a sector of cells in making the bandwidth reservation for accepting a new call. Based on the distance of the target cells in the sectors, two different bandwidth reservation policies are applied to optimize the connection dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…More research regarding call admission control, network planning, resource utilization, modelling, and retrial can be found in [12], [1,2,3,5,6,7,9,10,11,13,15,17,19,21,23,26,27,28,29,31,32]. Some works on modelling of arrival process, and retrial phenomenon based on generator matrix can be found in [4,14].…”
Section: Downloaded By [Colorado College] At 15:37 05 February 2015mentioning
confidence: 99%
“…More research regarding call admission control, network planning, resource utilization, modelling, and retrial can be found in [12], [1,2,3,5,6,7,9,10,11,13,15,17,19,21,23,26,27,28,29,31,32]. Some works on modelling of arrival process, and retrial phenomenon based on generator matrix can be found in [4,14].…”
Section: Downloaded By [Colorado College] At 15:37 05 February 2015mentioning
confidence: 99%
“…As in the case of propagation models, different mobility models are considered for different environments [6] . A pseudo-random mobility model with semidirected trajectories [5,7,8] is elaborated. In this model, the MTs are characterized by speed and direction and the Fig.…”
Section: Network Modelmentioning
confidence: 99%
“…Schemes using mobility prediction of a MT in bandwidth reservation can be classified as schemes using observation histories [7][8][9]12] and schemes using real time positioning techniques to predict the future path of MT [3][4][5][6]10,11,13]. The problem with the Schemes using observation histories to predict future path of MT is the overhead to develop, store and update traffic histories for the different cells [3].…”
mentioning
confidence: 99%
“…There has been a previous work that attempts to reserves a bandwidth in advance in the cell that a MT will visit it in the future. The Bandwidth reservation schemes can be categorized into schemes that reserve bandwidth in neighboring cells [1,2], in only one cell [3][4][5][6][7][8][9] and in a shadow of cluster [10][11][12][13]. Schemes reserving bandwidth in neighboring cells can be classified into schemes that reserve same bandwidth and schemes that reserve different bandwidth in each cell.…”
mentioning
confidence: 99%
See 1 more Smart Citation